Randomized Trial Comparing Adjuvant Intravitreal Triamcinolone Acetonide 2mg and Bevacizumab 12,5mg for Diabetic Macular Edema - maria Larasati; Arini Setiawati; Ari Djatikusumo (Medicinus, 2019)
ObjectivesTo evaluate the efficacy and safety of Intravitreal Triamcinolone Acetonide (IVTA) 2 mg and Bevacizumab (IVB) 12,5 mg for adjuvant therapy of Diabetic Macular Edema (DME)DesignThis was a prospective, randomized clinical trial. Each participants with DME was randomized to received single intravitreal injection of IVTA or IVB  and then being followed until fourth week after injection. The efficacy parameters were the improvement in Best Corrected Visual Acuity (BCVA) in logMAR and Standardized Central Macular Thickness (SCMT) by Optical Coherence Tomography. The safety parameters were the Intra Ocular Pressure (IOP) and Posterior Capsular cataract progression using LOCSIII criteria.ResultsTwenty five eyes of 20 participants were randomly assigned to receive IVTA 2 mg (n=12) and IVB (n=13). At 4 weeks, mean BCVA was better in IVTA group than in IVB group -0,39 logMAR (p<0,05). CMT reduction were significant in all visits of both groups. The SCMT showed 78,37%  at final follow-up for IVTA group. There were no statistic significant difference in the mean IOP and posterior capsular cataract changes among two groups. (p>0,05)ConclusionAdjuvant IVTA injections were more effective than IVB injections in patients with DME. However, it was associated with higher increment in IOP, despite not reaching statistical significance.